Friedrich Nietzsche: On Education. An Unfashionable Observation - Fernando BÁRCENA ORBE (Teoría de la Educación: Revista Interuniversitaria, 2016)
It is proposed in this paper an educational’ unfashionable observation, from an nietzschean point of view. The main purpose thinking about certain contemporary dispossession of the educational experiencie between generations. When the only thing to transmit is that which is soccialy demanded, the erosion of education as an unpredictable experience of Bildung turns out unavoidable. With the rise of the so called «Learning Society», the insistence on the democratic function of schoolastic education has been accompanied by a set of pedagogical demands, coming from society and the market, whose most immediate effect is a feeling of a suffocation on educational experience of apprenticeship. As is to be held in this text, education has to do, not with possibilities, but with the impossibilities, not with the continuities, but with interruptions, not only with action, but with passivity and delay.